STUDI BANDING TEKNOLOGI PENGOLAHAN LIMBAH CAIR PABRIK KELAPA SAWIT - Rahardjo, Pertus Nugro (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
In the last ten years Indonesia has already developed more than 15 CrudePalm Oil Factories (CPOF). Unfortunately the major of them do not have properwastewater treatment plants (WWTP) yet. General speaking that in Indonesia thepalm area has been increasing rapidly. Because of the very large palm area, almostall CPOF use a large area for the WWTP and the main processes of WWTP areanaerobic and aerobic system using large ponds as lagoons. The most environmentalproblems appear such as the bad quality of the effluent from WWTP and inmaintaining units of the WWTP. The aim of this assessment is to compare theWWTP belong to 3 CPOF (PT. Kertajaya, PTP Nusantara IV Bah Jambi and PT.Smart Tbk) and RANUT as a research product from Palm Research Center locatedin Medan. Wastewater (produced by CPOF) used for Land application is alsodiscussed and it is well known in using the wastewater to fertilize the palm plantation.A recommendation for the wastewater treatment system has been proposed. Thesystem has eight processes including oil separation or first sedimentation,neutralization, equalization, anaerobic degradation, aerobic degradation, finalsedimentation and sludge drying.